Coated titanium anodes with titanate interlayers, methods of making and using the same
Patent Information
- Application Number
- CN202311644510.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-04
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2043-12-04
AI Technical Summary
石墨电极虽然具有良好的导电性,但其在长时间使用过程中容易发生氧化、脱碳等问题,导致其稳定性不佳;合金电极常为铅电极或铝电极,应用范围小且环境污染严重;涂层钛阳极具有广泛的应用领域,可通过调节涂层成分实现选择电催化氧化与析氧的反应活性,同时可以耐受严苛的高温高酸性体系
[0014] In the embodiments of this disclosure, the sol-gel technology is used to assist in the salt immersion passivation and electrostatic adsorption loading process, and a two-step heat treatment method and an auxiliary insertion of an intermediate oxide layer to prepare the coated titanium anode. This overcomes the defect of short electrode life caused by oxide layer cracking during the drying and annealing process of the precursor. It achieves one-time dense coating of titanate layer, reduces the loading of precious metals, and has the advantages of low cost, low energy consumption, good product repeatability, and controllable quality. It is conducive to the expansion and practical application and development of coated titanium anodes in the field of industrial water electrochemical applications.
Smart Images

Figure CN117702166B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical anode plate technology, and particularly relates to a coated titanium anode with a titanate intermediate layer, its preparation method and application. Background Technology
[0002] In technologies such as electrocatalytic oxidation, electroplating, electrochemical cathodic protection, and electrolytic refining, the anodic reaction requires highly reactive and active anode materials. Commonly used anode materials in these technologies include graphite electrodes, alloy electrodes, and titanium-based coated anodes. While graphite electrodes possess good conductivity, they are prone to oxidation and decarburization during prolonged use, leading to poor stability. Alloy electrodes are often lead or aluminum electrodes, limiting their application range and causing significant environmental pollution. Coated titanium anodes have a wide range of applications, allowing for selective electrocatalytic oxidation and oxygen evolution reaction activity through coating composition adjustment, while also withstanding harsh high-temperature and high-acid systems.
[0003] Traditional methods for preparing coated titanium anodes involve multiple coating processes using metal salt solutions, followed by drying and sintering. However, the infrared drying and annealing processes are extremely energy-intensive, and the resulting noble metal coatings contain as much as 20 g / m³ of precious metals. 2 Meanwhile, improving stability by increasing coating thickness leads to a significant decrease in electrode activity. Therefore, traditional methods for preparing coated titanium anodes require high costs and energy-intensive processes, limiting their widespread application.
[0004] Therefore, it is necessary to develop a coated titanium anode with high anodic activity and strong stability and its preparation method, so as to promote the reduction of application cost of noble metal titanium anodes and the practical application of electrocatalytic oxidation, while achieving large-scale development. Summary of the Invention
[0005] In view of the above, in order to at least partially solve at least one of the aforementioned technical problems, this disclosure provides a coated titanium anode with a titanate interlayer, its preparation method and application. The preparation method of this disclosure has low preparation cost and low energy consumption. At the same time, the coated titanium anode product with a titanate interlayer prepared by the method of this disclosure has good repeatability and controllable quality. It is conducive to the expansion and practical application of coated titanium anodes in the field of industrial water electrochemical applications.
[0006] To solve the above-mentioned technical problems, the technical solution provided in this disclosure is as follows:
[0007] According to one aspect of this disclosure, a method for preparing a coated titanium anode having a titanate interlayer is provided, comprising:
[0008] A first metal source, a first sol, a first film-forming agent, and a first acid-base regulator are dispersed in an aqueous solution to obtain an intermediate layer sol solution, wherein the first metal source is a soluble salt of the first metal;
[0009] The titanium substrate is immersed in the intermediate layer sol solution and subjected to a first heat treatment, so that a first metal titanate intermediate layer is grown in situ on the surface of the titanium substrate.
[0010] The second metal source, the second sol, the second film-forming agent, and the second acid-base regulator are dispersed in an aqueous solution and then complexed by heating to obtain a surface catalytic layer sol solution, wherein the second metal source is a soluble salt of the second metal;
[0011] A titanium substrate with a titanate intermediate layer is immersed in a surface catalyst sol solution and subjected to a second heat treatment, which allows a second metal oxide catalyst layer to grow in situ on the surface of the titanate intermediate layer, resulting in a coated titanium anode.
[0012] According to another aspect of this disclosure, a coated titanium anode having a titanate intermediate layer is provided, obtained by the above-described method for preparing a coated titanium anode having a titanate intermediate layer.
[0013] According to another aspect of this disclosure, an application of the above-described coated titanium anode with a titanate intermediate layer in the field of electrochemistry of aqueous solution systems is provided.
[0014] In the embodiments of this disclosure, the sol-gel technology is used to assist in the salt immersion passivation and electrostatic adsorption loading process, and a two-step heat treatment method and an auxiliary insertion of an intermediate oxide layer to prepare the coated titanium anode. This overcomes the defect of short electrode life caused by oxide layer cracking during the drying and annealing process of the precursor. It achieves one-time dense coating of titanate layer, reduces the loading of precious metals, and has the advantages of low cost, low energy consumption, good product repeatability, and controllable quality. It is conducive to the expansion and practical application and development of coated titanium anodes in the field of industrial water electrochemical applications. Attached Figure Description
[0015] Figure 1 This is a flowchart of the method for preparing coated titanium anodes in this disclosure embodiment;
[0016] Figure 2 These are scanning electron microscope comparison images of the titanium substrate in Embodiment 1 of this disclosure. (a) and (b) are before and after the titanium substrate pretreatment, respectively.
[0017] Figure 3 This is the X-ray diffraction pattern of the manganese titanate intermediate layer prepared in Example 1 of this disclosure;
[0018] Figure 4 This is the X-ray diffraction pattern of the diffraction peaks of MnTiO3 and Ti;
[0019] Figure 5 This is a low-resolution transmission electron microscope image of the manganese titanate intermediate layer prepared in Example 1 of this disclosure;
[0020] Figure 6 This is a high-resolution transmission electron microscope image of the manganese titanate intermediate layer prepared in Example 1 of this disclosure;
[0021] Figure 7 This is an elemental analysis chart of the manganese titanate intermediate layer prepared by energy dispersive spectroscopy in Example 1 of this disclosure;
[0022] Figure 8 These are scanning electron micrographs of the manganese titanate intermediate layer prepared in Example 1 of this disclosure. (a) is a low-resolution scanning electron micrograph, and (b) is a high-resolution scanning electron micrograph.
[0023] Figure 9 These are transmission electron microscope (TEM) images of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure. (a) is a low-resolution TEM image, and (b) is a high-resolution TEM image.
[0024] Figure 10 This is a low-resolution transmission electron microscope image of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure;
[0025] Figure 11 This is a high-resolution transmission electron microscope image of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure. (a) and (b) show different positions.
[0026] Figure 12 This is an elemental analysis chart of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure using an energy dispersive spectroscopy (EDS) instrument.
[0027] Figure 13 The following are X-ray photoelectron spectroscopy (XPS) spectra of the noble metal coated titanium anode with a manganese titanate interlayer prepared in Example 1 of this disclosure: (a) is a comparison of XPS spectra of the manganese titanate interlayer prepared in Example 1 of this disclosure with that of MnO2; (b) is a comparison of XPS spectra of the manganese titanate interlayer prepared in Example 1 of this disclosure with that of TiO2; (c) is an XPS spectra of the O1s orbital fitting curve in the noble metal oxide catalyst layer prepared in Example 1 of this disclosure; (d) is an XPS spectra of the Ir 4f orbital fitting curve in the noble metal oxide catalyst layer prepared in Example 1 of this disclosure; and (e) is an XPS spectra of the Ru 3p orbital fitting curve in the noble metal oxide catalyst layer prepared in Example 1 of this disclosure.
[0028] Figure 14 These are the operational stability test diagrams for Embodiment 2 and Comparative Example 3 of this disclosure;
[0029] Figure 15This is a scanning electron microscope image of a tin-lead coated titanium anode with a manganese titanate interlayer prepared according to Example 3 of this disclosure;
[0030] Figure 16 This is a test diagram of the tin-lead coated titanium anode resistance performance with a manganese titanate intermediate layer obtained in Example 3 of this disclosure;
[0031] Figure 17 This is a comparison diagram of the removal effect of the tin-lead coated titanium anode with manganese titanate intermediate layer prepared in Example 3 of this disclosure and that of Comparative Example 4 on bromophenol removal. Detailed Implementation
[0032] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments and the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this disclosure.
[0033] The terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit this disclosure. The terms “comprising,” “including,” etc., as used herein indicate the presence of the stated features, steps, operations, and / or components, but do not exclude the presence or addition of one or more other features, steps, operations, or components.
[0034] Similarly, to simplify this disclosure and aid in understanding one or more of the various aspects of the disclosure, in the above description of exemplary embodiments of the present disclosure, various features of the present disclosure are sometimes grouped together in a single embodiment, figure, or description thereof. The use of terms such as "one embodiment," "some embodiments," "example," "specific example," or "some examples," etc., refers to a specific feature, structure, material, or characteristic described in connection with that embodiment or example, which is included in at least one embodiment or example of the present disclosure. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.
[0035] Furthermore, the terms "first," "second," etc., are used for descriptive purposes only and should not be construed as indicating or implying relative importance or implicitly specifying the number of technical features indicated. Therefore, a feature defined as "first" or "second" may explicitly or implicitly include one or more of that feature. In the description of this disclosure, "a plurality of" means at least two, such as two, three, etc., unless otherwise explicitly specified.
[0036] In addition, the technical solutions of various embodiments may be combined with each other, but it must be based on what can be achieved by a person skilled in the art. When the combination of technical solutions is contradictory or cannot be achieved, it should be considered that such a combination of technical solutions does not exist, and is not within the protection scope required by the present disclosure.
[0037] Dimensionally Stable Anode (DSA) is an anode material that uses titanium as a substrate (mesh, plate, strip, tube, etc.), and a noble metal coating is brushed on the titanium substrate, so that it has good electrocatalytic activity and electrical conductivity; titanium anodes are differentiated according to the gas precipitated at the anode in electrochemical reactions, those that precipitate chlorine are called chlorine evolution anodes, such as ruthenium-based coated titanium electrodes, and those that precipitate oxygen are called oxygen evolution anodes, such as iridium-based coated titanium electrodes and platinum titanium mesh / plates.
[0038] However, when adding functional metals in the traditional manufacturing process of coated titanium anodes, the amount of noble metals such as ruthenium and iridium is large and the required energy consumption is high. Meanwhile, improving the stability by increasing the coating thickness will lead to a serious reduction in electrode activity. Therefore, a preparation process of coated titanium anodes with lower cost, better stability and more excellent performance is needed.
[0039] In order to solve the above technical problems, the present disclosure prepares a coated titanium anode with a titanate interlayer and an application thereof through a preparation method of a coated titanium anode with a titanate interlayer, wherein the coated titanium anode comprises a titanium matrix, a titanate interlayer and a surface catalytic active layer. The titanate interlayer has MTiO3 or M x Ti 1-x O3 (0<x<1), with the general formula (M is a transition metal element, such as manganese, cobalt, copper, tin, etc.), which is located between the titanium matrix and the surface catalytic layer, and has stable bonding with both; the surface catalytic layer is uniformly dispersed on the titanate interlayer; the titanate interlayer can form chemical bonding with both the titanium matrix and the surface catalytic layer, and at the same time, its own semiconductor property can enhance the electrochemical performance of the surface catalytic layer, and synergistically enhance the activity and stability of the anode.
[0040] According to an embodiment of one aspect of the present disclosure, there is provided a method for preparing a coated titanium anode having a titanate interlayer, Figure 1 is a flow chart of the titanium anode preparation method of the present disclosure:
[0041] Step S1: dispersing a first metal source, a first sol agent, a first film-forming agent, and a first acid-base regulator in an aqueous solution, fully dissolving them at 20-25°C to obtain an interlayer sol solution, and standing for aging for 1-3h for later use, wherein the first metal source is a soluble salt of the first metal;
[0042] Step S2: Immerse the titanium substrate in the intermediate layer sol solution and perform a first heat treatment to grow a first metal titanate intermediate layer in situ on the surface of the titanium substrate.
[0043] Step S3: Disperse the second metal source, the second sol, the second film-forming agent, and the second acid-base regulator in an aqueous solution, and perform complexation by heating to obtain a surface catalyst layer sol solution. Cool and let stand for aging for 1-3 hours for later use. The second metal source is a soluble salt of the second metal.
[0044] Step S4: Immerse the titanium substrate with the titanate intermediate layer into the surface catalyst layer sol solution and perform a second heat treatment to grow a second metal oxide catalyst layer in situ on the surface of the titanate intermediate layer, thereby obtaining a coated titanium anode.
[0045] In some embodiments of the present invention, in step S1, the titanium substrate is one of the following: woven titanium mesh (20 mesh, 50 mesh, 100 mesh, 200 mesh, 300 mesh and 600 mesh), titanium foil, perforated mesh, foamed titanium plate, titanium tube and titanium wire mesh.
[0046] According to embodiments of this disclosure, a coated titanium anode prepared by employing sol-gel technology to assist in salt immersion passivation and electrostatic adsorption loading processes, a two-step heat treatment method, and the auxiliary insertion of an intermediate oxide layer overcomes the defect of short electrode life caused by oxide layer cracking during the drying and annealing process of the precursor. It achieves one-time dense coating of titanate layer and inhibits the formation of insulating titanium dioxide (TiO2) film. The formation process of the surface catalyst layer can chemically interact with titanate to synergistically enhance the electrochemical activity and stability of the surface catalyst layer, while reducing the loading of noble metals. It has the advantages of low cost, low energy consumption, good product repeatability, and controllable quality.
[0047] According to embodiments of this disclosure, the first metal is selected from at least one of fourth-period transition elements and tin; the second metal is selected from at least one of noble metal elements and tin and lead.
[0048] The first metal source is added in the form of a nitrate or chloride of a first metal, preferably a 50 wt% Mn(NO3)2 solution, MnSO4, CoCl2, Co(NO3)2·6H2O, CuCl2, or Cu(NO3)2·3H2O; the second metal is added in the form of a nitrate or chloride of a second metal, preferably IrCl3, Na3IrCl6, Na2IrCl6, RuCl3, or Ru(NO)(NO3)3.
[0049] According to embodiments of this disclosure, the titanate interlayer formed by the transition element has a stable chemical bond with both the titanium substrate and the surface catalyst layer. At the same time, its own semiconductor properties can enhance the electrochemical performance of the surface catalyst layer, synergistically enhancing the activity and stability of the titanium anode. Meanwhile, since the fourth-period elements have smaller molecular weights, they can better bond to form the titanate interlayer structure. Therefore, the first metal is selected from at least one of the fourth-period transition elements and tin, which can also form a stable chemical bond and has a suitable molecular weight.
[0050] The second metal is selected based on the specific application scenario. For example, when using coated titanium anodes for oxygen evolution reaction, noble metals iridium (Ir) and ruthenium (Ru) can be selected as the second metal to prepare the surface catalytic layer. Alternatively, for non-oxygen evolution reaction, tin (Sn) and lead (Pb) can be selected as the second metal to prepare the surface oxide layer. The metal element selected should be functional and its oxide should be insoluble in acids and alkalis, depending on the specific application scenario.
[0051] The first and second metals are each added in the form of their soluble salts, either nitrates or chlorides, which can be adapted to sol-gel technology to assist in the salt leaching passivation and electrostatic adsorption loading process.
[0052] According to embodiments of this disclosure, in step S3, the complexing agent that can be added is at least one of citric acid, sodium citrate, and potassium citrate; in steps S1 and S3, the first film-forming agent and the second film-forming agent are each independently at least one of polyethylene glycol (PEG), polyvinyl alcohol, alcohol ethers, and acrylic copolymer emulsions, with a molecular weight between 600 and 2000; the first sol and the second sol are each independently at least one of polyvinylpyrrolidone (PVP), ethylene glycol, ethylene oxide, and triethanolamine, with a molecular weight between 400,000 and 1,300,000; the first acid-base adjuster and the second acid-base adjuster are each independently at least one of 3wt% dilute nitric acid (HNO3), dilute hydrochloric acid, dilute sulfuric acid, and acetic acid, and the alkali is each independently at least one of 0.2wt% dilute ammonia (NH3·H2O), potassium monohydrogen phosphate, and sodium monohydrogen phosphate.
[0053] The addition of complexing agents can enable metal ions to form complexes with ligand molecules, thereby forming stable complexes and preventing metal precipitation; the addition of film-forming agents can form a protective film layer on the electrode; the addition of sol-gel agents can protect the metal from reacting into its oxides, making it more stable, while also making the particles in the sol more uniformly dispersed; the addition of acid-base adjusters can adjust the pH value to the required reaction value without affecting the properties of the sol solution.
[0054] According to embodiments of this disclosure, the titanium substrate is pretreated before being immersed in the intermediate layer sol solution. The pretreatment includes the following steps:
[0055] The titanium substrate is cleaned, etched, and then stored in an oxygen-free environment for later use.
[0056] The cleaning process for the titanium substrate involves using an organic system of soda ash for degreasing, and the etching method is acid etching.
[0057] In some embodiments of this disclosure, the cleaning method is as follows:
[0058] The titanium substrate was immersed in acetone under ultrasonic conditions, then rinsed with deionized water, and then placed in a hot alkaline solution, and finally rinsed with deionized water. The ultrasonic immersion time was 20-60 minutes, the hot alkaline solution was a solution with a temperature of 80-100℃ and a sodium carbonate concentration of 100-250 g / L, and the hot alkaline solution treatment time was 0.5-2 hours.
[0059] In some embodiments of this disclosure, the etching method is as follows:
[0060] The titanium matrix is treated with a non-oxidizing acid under heating conditions. The non-oxidizing acid is at least one of dilute hydrochloric acid, dilute sulfuric acid, and oxalic acid, with an acid concentration of 5-15 wt%, a heating temperature of 80-100℃, and a treatment time of 1.5-3 h.
[0061] The pretreated titanium substrate has a rough active metal surface, which removes insulating oxide components and improves surface hydrophilicity, making it easier to coat. This improves the surface coating degree of titanate oxides loaded during the salt immersion passivation process and the uniformity of the pyrolysis reaction.
[0062] According to an embodiment of this disclosure, in step S3, the temperature for heating and complexation is 50-60°C;
[0063] According to an embodiment of this disclosure, in step S2, the operation of the first heat treatment includes:
[0064] The titanium matrix impregnated with the intermediate sol solution is dried and calcined. The drying is divided into initial drying and final drying. The initial drying temperature is 20-25℃ and the drying time is 4-5h. The final drying temperature is 40-60℃ and the drying time is 15-30min. Preferably, the final drying temperature is 50℃.
[0065] The roasting temperature is 300-500℃, for example, 300℃, 350℃, 400℃, 450℃, 500℃, etc., and the roasting time is 1.5-3h. Preferably, the roasting temperature is 350-400℃ and the roasting time is 2-2.5h.
[0066] The titanium matrix impregnated with the intermediate sol solution after drying and calcination is subjected to a cooling reduction. The cooling reduction step is carried out at a temperature of 100-300℃, such as 100℃, 150℃, 200℃, 250℃, 300℃, etc., in a hydrogen-argon mixture atmosphere, for a reduction time of 1-3 hours. Preferably, the temperature is 200-250℃ and the calcination time is 1.5-2 hours.
[0067] Low-temperature reduction can optimize the uniformity of titanate layer coating and improve the protection of titanium substrate.
[0068] According to an embodiment of this disclosure, in step S4, the second heat treatment operation includes:
[0069] The titanium substrate with a titanate intermediate layer grown after being immersed in the surface catalyst sol solution is dried and calcined. The drying is divided into initial drying and final drying. The initial drying temperature is 20-25℃ and the initial drying time is 4-5h. The final drying temperature is 40-60℃ and the final drying time is 15-30min. Preferably, the final drying temperature is 50℃.
[0070] The high-temperature calcination process parameters are 350-500℃, for example, 350℃, 400℃, 450℃, 500℃, etc., and the calcination time is 0.5-2h; preferably, the final drying temperature is 50℃, the calcination temperature is 400-450℃, and the calcination time is 1-1.5h.
[0071] According to embodiments of this disclosure, in steps S2 and S4, the impregnation can be a reaction at room temperature, for example, a reaction at 20-25°C for 2-3 hours.
[0072] Through the impregnation process, the intermediate layer sol solution is adsorbed and loaded onto the titanium substrate relatively uniformly, and the surface catalyst layer sol solution is loaded onto the titanate intermediate layer relatively uniformly.
[0073] According to embodiments of this disclosure, in steps S1 and S2, the amounts of the first and second acid-base adjusters are such that the pH of the prepared intermediate layer sol solution is between 1.5 and 2.5, and the pH of the surface catalyst layer sol solution is between 5 and 7.
[0074] The surface zero-point charge of the titanium matrix has a pH value of 4. In environments with a pH value below 4, the titanium matrix surface can enhance the adsorption of cations, namely the first metal source cations, such as Mn. 2+ The surface zero-point charge of the titanate interlayer is 3, and it can enhance the adsorption of anions, i.e., complex anions containing a second metal source, such as [IrCl4], in environments with a pH value higher than 3. 2- and [RuCl3(OH)] - .
[0075] According to embodiments of this disclosure, the total content of the first metal source in the intermediate layer sol solution is 5%-20wt%.
[0076] In the catalyst layer sol solution, the total content of the second metal source is 5%-20wt%;
[0077] The molar ratio of the complexing agent to the second metal source metal element is 0.6-1.0:1, preferably 0.7-0.9:1.
[0078] Adding too little metal source will result in uneven and insufficient coating and cracks, while adding too much metal source will result in waste and increase preparation costs; adding too little complexing agent will result in metal precipitation, while adding too much will result in waste and increase preparation costs.
[0079] According to embodiments of this disclosure, in the intermediate layer sol solution, the ratio of the prepared intermediate layer sol solution (ml): the mass of the added sol agent (g): the mass of the film-forming agent (g) is 1:0.02-0.10:0.02-0.10, preferably 1:0.04-0.06:0.04-0.06.
[0080] In the surface catalytic layer sol solution, the ratio of surface catalytic layer sol solution (ml): sol mass (g): film-forming agent mass (g) is 1:0.02-0.10:0.02-0.10, preferably 1:0.04-0.06:0.04-0.06.
[0081] According to another aspect of this disclosure, a coated titanium anode having a titanate intermediate layer is provided, obtained by the above-described method for preparing a coated titanium anode having a titanate intermediate layer.
[0082] The titanium anode with a titanate interlayer prepared by the method disclosed herein has a good coating effect. The electrode coated with the titanate interlayer can effectively suppress the formation of the insulating TiO2 film, and at the same time, the dissolution of the surface catalyst layer components can be well suppressed. The electrode has high activity and good stability.
[0083] According to another aspect of this disclosure, an application of the above-described coated titanium anode with a titanate intermediate layer in the field of electrochemistry of aqueous solution systems is provided.
[0084] To make the objectives, technical solutions, and advantages of this disclosure clearer, the following detailed description is provided in conjunction with specific embodiments.
[0085] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available. Methods not specifically described in the examples are conventional and can be performed according to the techniques or conditions described in the literature or the product instructions.
[0086] Examples of embodiments of this disclosure are illustrated below:
[0087] Example 1
[0088] The steps for preparing a noble metal coated titanium anode with a manganese titanate interlayer are as follows: Figure 1 As shown:
[0089] Pretreatment: Using titanium plates, titanium meshes, or titanium punch plates (i.e., titanium substrates), the titanium plates need to be polished sequentially with 300-grit and 600-grit sandpaper, immersed in acetone and repeatedly ultrasonically cleaned, then placed in a 25g / L sodium carbonate (Na2CO3) solution heated to 100℃ for 1 hour, followed by a simple rinse with tap water. Then, it is placed in a 2.5wt% oxalic acid solution at 95℃ for 1.5 hours of gentle boiling etching. After cooling, the etched titanium plate is rinsed thoroughly with plenty of water until the matte metal surface is exposed and stored in clean water for later use. This process involves cleaning and etching. A comparison of the titanium substrate before and after pretreatment is provided. Figure 2 As shown.
[0090] Step S1: Dissolve 28 ml of 50 wt% manganese nitrate solution (the first metal source), 8 ml of 0.5 mol / L dilute nitric acid (the first acid-base regulator), 6 g of polyethylene glycol (M2000) (the first film-forming agent), and 12 g of polyvinylpyrrolidone (M1300000) (the first sol) in 200 ml of water. Stir at room temperature for 30 min, let stand and age for 1 h, and then apply to obtain the intermediate layer sol solution.
[0091] Step S2: The titanium substrate is uniformly immersed in the intermediate layer sol solution prepared in step S1, and allowed to stand for 2 hours to obtain a salt-passivated titanium substrate surface and a sol layer of suitable thickness. The remaining sol on the surface is simply shaken off, and the substrate is dried in air for 3 hours, then dried in a 60℃ oven for 30 minutes. It is then placed in a muffle furnace and calcined at 350℃ for 2 hours. After cooling to room temperature, it is thermally reduced at 200℃ for 2 hours under a hydrogen-argon mixed atmosphere, i.e., the first thermal reaction, to prepare a manganese titanate intermediate layer titanium anode. Relevant tests are performed, and the test results are as follows: Figure 3-8 As shown in Table 1.
[0092] Step S3: Dissolve 0.6 mmol of sodium chloroiridate (Na2IrCl4) (the second metal source), 1.5 mmol of ruthenium trichloride (RuCl3) (the second metal source), 0.8 ml of 0.5 mol / L dilute nitric acid (the second acid-base regulator), 1.7 mmol of citric acid (the complexing agent), 1.2 g of polyethylene glycol (M2000) (the second film-forming agent), and 0.6 g of polyvinylpyrrolidone (M1300000) (the second sol) in 15 ml of deionized water. Stir and react at 60°C for 2 hours. After evaporating 5 ml, allow the mixture to stand and age for 1 hour before coating to obtain the surface catalyst layer sol solution.
[0093] Step S4: The oxygen-evolving active iridium-ruthenium noble metal catalyst sol was uniformly coated onto the manganese titanate intermediate layer titanium anode. The remaining sol was simply shaken off, and the anode was air-dried for 3 hours, then dried in a 60°C oven for 30 minutes. Next, it was placed in a muffle furnace for thermal decomposition at 450°C for 1.5 hours (the second thermal reaction). After cooling to room temperature, the noble metal-coated titanium anode with a manganese titanate intermediate layer was obtained. Relevant tests were performed, and the results are as follows: Figure 9-13 As shown in Table 2.
[0094] Comparative Example 1
[0095] An iridium-coated titanium anode with a manganese titanate interlayer
[0096] Dissolve 0.6 mmol of Na2IrCl4, 0.8 ml of 0.5 mol / L dilute nitric acid, 1.7 mmol of citric acid, 1.2 g of polyethylene glycol (M2000), and 0.6 g of polyvinylpyrrolidone (M1300000) in 15 ml of deionized water. Stir the mixture at 60°C for 2 hours. After evaporating 5 ml of the solution, allow it to stand for 1 hour before applying.
[0097] The oxygen evolution active catalyst layer iridium noble metal precursor sol was uniformly coated onto the manganese titanate intermediate layer. The same steps were used to thermally decompose it in a muffle furnace at 450℃ for 90 min. After cooling to room temperature, an iridium noble metal coated titanium anode with a manganese titanate intermediate layer was obtained.
[0098] Comparative Example 1 will be used for characterizing the electronic structure properties in Example 1.
[0099] Comparative Example 2
[0100] A ruthenium noble metal coated titanium anode with a manganese titanate interlayer
[0101] Dissolve 1.5 mmol RuCl3, 0.8 ml 0.5 mol / L dilute nitric acid, 1.7 mmol citric acid, 1.2 g polyethylene glycol (M2000), and 0.6 g polyvinylpyrrolidone (M1300000) in 15 ml deionized water. Stir at 60°C for 2 hours. After evaporating 5 ml, let stand for 1 hour before applying.
[0102] The ruthenium noble metal precursor sol of the oxygen evolution active catalyst layer was uniformly coated on the manganese titanate intermediate layer. The same steps were used to thermally decompose it in a muffle furnace at 450℃ for 90 min. After cooling to room temperature, a ruthenium noble metal coated titanium anode with a manganese titanate intermediate layer was obtained.
[0103] Comparative Example 2 will be used for characterizing the electronic structure properties in Example 1.
[0104] Figure 2These are scanning electron microscope (SEM) comparison images of the titanium substrate before and after pretreatment in Example 1 of this embodiment.
[0105] in, Figure 2 (a) is a scanning electron microscope image of the titanium matrix before pretreatment. Figure 2 (b) is a scanning electron microscope image of the pretreated titanium substrate.
[0106] Depend on Figure 2 It can be seen that the surface of the titanium substrate is etched from the original smooth surface to a rough surface. At the same time, the oxide components on the original surface are significantly removed after etching, and the surface hydrophilicity is further improved. The excellent hydrophilicity of the surface is conducive to the coating operation. The removal of surface oxides can enable the subsequent formation of a more uniform and dense titanate layer, thereby improving the electrode activity and stability.
[0107] Figure 3 This is the X-ray diffraction pattern of the titanium anode with a manganese titanate interlayer obtained in Example 1.
[0108] The diffraction peaks of the titanium anode with the manganese titanate interlayer prepared in the examples were detected on X-ray diffraction (XRD) patterns, which can be used to determine the diffraction peaks. Figure 3 The XRD diffraction pattern shows diffraction peaks at 2θ angles of 20.8°±0.2°, 23.5°±0.2°, 34.9°±0.2° and 48.1°±0.2°, proving that the titanium anode intermediate layer of Example 1 is composed of manganese titanate.
[0109] Figure 4 The XRD diffraction peak positions of pure MnTiO3 and Ti are shown. The XRD diffraction pattern of MnTiO3 has diffraction peaks at 2θ angles of 23.6°±0.2°, 32.1°±0.2°, 35.0°±0.2°, 39.8°±0.2° and 41.0°±0.2°, and the XRD diffraction pattern of Ti has diffraction peaks at 2θ angles of 35.2°±0.2°, 37.0°±0.2° and 20.5°±0.2°. Example 1 clearly matches the diffraction peak characteristics of both, proving that the intermediate layer is composed of manganese titanate.
[0110] Figure 5 This is a low-resolution transmission electron microscope (TEM) image of the manganese titanate intermediate layer prepared in Example 1, with a resolution of 50 nm. The nanoparticle sizes shown are concentrated in the range of 20–30 nm, consistent with the scanning electron microscope (SEM) image.
[0111] Figure 6This is a high-resolution transmission electron microscope (TEM) image of the manganese titanate intermediate layer prepared in Example 1, with a resolution of 2 nm. From the TEM image of the manganese titanate intermediate layer, it can be seen that the lattice fringes of the titanium dioxide oxide film are not obvious or do not exist, while the lattice fringes of manganese titanate are obvious. The two types of lattice fringes with spacing of 0.188 nm and 0.425 nm in the TEM image correspond to the (024) and (101) crystal planes of manganese titanate, which are consistent with the standard PDF card data in XRD phase analysis. The thickness of the composite oxide intermediate layer is less than 100 nm, as can be seen from the intensity of the diffraction peaks in the spectrum.
[0112] Figure 7 This is the elemental analysis diagram of the manganese titanate intermediate layer prepared in Example 1 using an energy dispersive spectrometer.
[0113] Table 1 shows the elemental content of the manganese titanate intermediate layer elemental spectrometer prepared in Example 1 of this invention.
[0114]
[0115] according to Figure 7 As shown in Table 1, the atomic ratio of oxygen, titanium and manganese in the manganese titanate intermediate layer prepared in Example 1 is approximately 3:1:1, which is consistent with the atomic ratio of manganese titanate (MnO3Ti).
[0116] Figure 8 (a) is a low-resolution scanning electron micrograph of the manganese titanate intermediate layer prepared in this embodiment, with a resolution of 200 nm;
[0117] Figure 8 (a) is a high-resolution scanning electron micrograph of the manganese titanate intermediate layer prepared in this embodiment, with a resolution of 1 μm;
[0118] according to Figure 8 (a) and Figure 8 (b) It can be seen that the prepared manganese titanate intermediate layer is uniformly coated on the surface of the titanium substrate, without obvious damage or cracks.
[0119] Figure 9 (a) is a low-resolution scanning electron micrograph of the noble metal oxide catalyst layer prepared in this embodiment, with a resolution of 200 nm;
[0120] Figure 9 (b) is a high-resolution scanning electron micrograph of the noble metal oxide catalyst layer prepared in this embodiment, with a resolution of 1 μm;
[0121] according to Figure 9 (a) and Figure 9 (b) It can be seen that the obtained precious metal oxide thin layer is densely coated on the surface of the manganese titanate intermediate layer, without obvious damage or cracks.
[0122] Figure 10This is a low-resolution transmission electron microscope image (TEM) of the noble metal oxide catalyst layer prepared in this embodiment, with a resolution of 50 nm, showing the uniform coating of noble metal on the surface of manganese titanate particles.
[0123] Figure 11 (a) and Figure 11 (b) is a high-resolution transmission electron microscope (TEM) image of the noble metal oxide catalyst layer prepared in this embodiment at different locations. The resolution is 2 nm. The lattice fringe spacing in the TEM image is 0.197 nm, 0.142 nm, 0.135 nm, and 0.201 nm, which correspond to the (112) and (310) crystal planes of RuO2 and the (301) and (210) crystal planes of IrO2, respectively.
[0124] Figure 12 This is the elemental analysis diagram of the noble metal oxide catalyst layer prepared in Example 1 using an energy dispersive spectroscopy (EDS) instrument.
[0125] Table 2 is a table of elemental contents of the noble metal oxide catalyst layer obtained in Example 1.
[0126]
[0127] according to Figure 12 As shown in Table 2, the atomic ratio of oxygen, titanium, and manganese in the noble metal oxide catalyst layer prepared in Example 1 is approximately 3:1:1, which is consistent with the atomic ratio of manganese titanate (MnO3Ti), and also contains a small amount of Ru and Ir elements.
[0128] Figure 13 (a)~ Figure 13 (e) is the X-ray photoelectron spectroscopy analysis diagram of the noble metal coated titanium anode with manganese titanate intermediate layer prepared in Example 1, which shows the electronic interaction between the manganese titanate intermediate layer and the noble metal catalytic active layer.
[0129] Figure 13 (a) is a comparison diagram of X-ray photoelectron spectroscopy analysis of the manganese titanate intermediate layer prepared in Example 1 and MnO2;
[0130] The difference between the manganese titanate interlayer and the MnO2 coating layer can be seen. The Mn 2p orbital values are obtained from the fitting curves of the Mn 2p orbitals and Ti 2p orbitals. 3 / 2 The binding energy position is 640.7 eV, with a distinct divalent satellite peak.
[0131] Figure 13 (b) is a comparison diagram of X-ray photoelectron spectroscopy analysis of the manganese titanate intermediate layer and TiO2 prepared in Example 1 of this disclosure;
[0132] It can be seen that the difference in binding energy between the Ti 2p orbital splitting peaks is less than the standard deviation of the binding energy of the Ti 2p orbital splitting crack in TiO2, which is 5.9 eV, proving the chemical interaction relationship between Mn and Ti.
[0133] Figure 13 (c) is the X-ray photoelectron spectrum of the O1s orbital fitting curve in the noble metal oxide catalyst layer prepared in Example 1 of this disclosure;
[0134] It can be seen that the O1s orbital fitting curve in the noble metal catalytic active layer corresponds to the "metal-O" bond. Compared with the noble metal layer in the noble metal coated titanium anode without the manganese titanate intermediate layer in Example 1, the position of the strongest binding energy peak has shifted significantly, proving the electronic interaction between the noble metal layer and the manganese titanate intermediate layer.
[0135] Figure 13 (d) is the X-ray photoelectron spectrum of the Ir 4f orbital fitting curve of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure;
[0136] It can be seen from the fitting curves of the Ir 4f orbitals in the noble metal catalytic active layer that the noble metal catalytic active layers without Ru in Example 1 and Comparative Example 1 show inconsistencies in the Ir valence state. The Ir 4f orbitals without Ru... 7 / 2 The orbital peaks are relatively broad, and the binding energy tends to be IrO2. In Example 1, Ir 4f... 7 / 2 The orbital peak is relatively narrow, concentrated at 62.5 eV, and the binding energy tends to be IrO. x Between IrO2.
[0137] Figure 13 (e) is the X-ray photoelectron spectrum of the Ru 3p orbital fitting curve of the noble metal oxide catalyst layer prepared in Example 1 of this disclosure;
[0138] It can be seen that the noble metal catalytic active layer of Example 1 and the noble metal catalytic active layer without Ir in Comparative Example 2 show inconsistencies in the Ru valence state. In Comparative Example 2, Ru 3p 3 / 2 The orbital peak binding energies of 462.8 eV and 465.0 eV correspond to RuO, respectively. x With RuO2, and Ru 3p in Example 2 3 / 2 The orbital peak is relatively narrow, concentrated at 464.2 eV, and the binding energy tends to be around RuO. x With RuO2, binding Figure 13 The lowest binding energy position obtained from the O1s orbital fitting curve in (a) proves that there is a significant interaction between Ir and Ru in the surface catalytic active layer.
[0139] Example 2
[0140] The resistance was measured by electrolyzing water using a noble metal-coated titanium anode with a manganese titanate interlayer prepared in Example 1.
[0141] The oxygen evolution activity of the test electrode was tested using an electrochemical workstation. A three-electrode system was used, with the working electrode being a 2.0 cm × 1.0 cm noble metal coated titanium anode electrode with a manganese titanate intermediate layer prepared in Example 1, the counter electrode being a carbon plate electrode, the reference electrode being a silver / silver chloride electrode (Ag / AgCl), and the electrolyte being 5 wt% dilute sulfuric acid.
[0142] Comparative Example 3
[0143] A noble metal coated titanium anode with a manganese titanate interlayer is prepared using a non-sol-gel method.
[0144] Dissolve 0.6 mmol of Na2IrCl4 and 1.5 mmol of RuCl3 in 15 ml of deionized water, stir at 60°C for 2 h, evaporate 5 ml, let stand for 1 h, and then apply.
[0145] The oxygen evolution active catalyst layer iridium-ruthenium noble metal precursor sol was uniformly coated onto the manganese titanate intermediate layer of Example 1. The same steps were used to thermally decompose it in a muffle furnace at 450°C for 90 min. After cooling to room temperature, a ruthenium noble metal coated titanium anode with a manganese titanate intermediate layer was obtained.
[0146] Comparative Example 3 will be used to verify the stability of acidic electrolyzed water in Example 2.
[0147] Figure 14 Examples 2 and 3 were compared at 2000 A / m 2 Stability test diagram under operating conditions.
[0148] The linear sweep voltammetry test was conducted with an initial potential of 0V and an endpoint potential of 2.3V at a scan rate of 10mV / s. Prior to the linear sweep voltammetry test, the electrode was activated and stabilized using cyclic voltammetry scanning within a range of 0V to 1.8V. The scan rate was 20mV / s, and 20 cycles were performed. The test results showed that, under a current density of 10mA / cm², the oxygen evolution overpotential of the newly prepared electrode was 196mV. Figure 13 As shown in Example 3, under the condition of a current density of 2000 A / m2, the voltage of the electrolytic cell with the newly made electrode at the anode is 1.78 V, and the voltage increases by 0.1 V after running for 3520 h; under the conditions of a current density of 8000 A / m2, a reaction temperature of 50 °C, and a stirring speed of 300 rpm, the voltage increases by 0.1 V after running stably for 800 h, indicating that the electrolytic water of Example 2 of this disclosure has good stability.
[0149] Example 3
[0150] The steps for preparing a tin-lead coated titanium anode with a manganese titanate interlayer are as follows: Figure 1 As shown:
[0151] Pretreatment: Use titanium plates, titanium meshes, or titanium punch plates, i.e., titanium substrates. The titanium plates need to be polished with 300-grit and 600-grit sandpaper in sequence, soaked in acetone and ultrasonically cleaned repeatedly, placed in a 25g / L sodium carbonate (Na2CO3) solution heated to 100℃ for 1 hour, and then rinsed with tap water to remove the Na2CO3 solution. Then, place the plate in a 2.5wt% oxalic acid solution at 95℃ for 1.5 hours of gentle boiling etching. After cooling, rinse the etched titanium plate with plenty of water until the matte metal surface is exposed and store it in water for later use. This process involves cleaning and etching.
[0152] Step S1: Dissolve 28 ml of 50 wt% manganese nitrate solution (the first metal source), 8 ml of 0.5 mol / L dilute nitric acid (the first acid-base regulator), 6 g of polyethylene glycol (M2000) (the first film-forming agent), and 12 g of polyvinylpyrrolidone (M1300000) (the first sol) in 200 ml of water. Stir at room temperature for 30 min, let stand and age for 1 h, and then apply to obtain the intermediate layer sol solution.
[0153] Step S2: The titanium substrate is uniformly immersed in the intermediate layer sol solution prepared in step S1, and left to stand for 2 hours to obtain a salt-passivated titanium substrate surface and a suitable sol thickness layer. The remaining sol on the surface is simply shaken off, and the substrate is placed in an air environment to dry for 3 hours. Then it is dried in a 60°C oven for 30 minutes, and then placed in a muffle furnace to calcine at 350°C for 2 hours. After being taken out and cooled to room temperature, it is thermally reduced at 200°C for 2 hours in a hydrogen-argon mixed atmosphere to prepare a manganese titanate intermediate layer titanium anode.
[0154] Step S3: Dissolve 12 mmol tin tetrachloride (SnCl4·5H2O) (the second metal source), 6 mmol lead nitrate (Pb(NO3)2) (the second metal source), 2.4 g polyethylene glycol (M2000) (the second film-forming agent), 0.4 ml 0.5 mol / L dilute nitric acid (the second acid-base regulator), and 0.4 g polyvinyl alcohol (the second sol) in 10 ml deionized water. Stir at 60°C for 2 hours, let stand and age for 1 hour, and then apply to obtain the surface catalyst layer sol solution.
[0155] Step S4: The non-oxygen-evolving active tin-lead catalyst sol is uniformly coated onto the manganese titanate intermediate layer titanium anode. The remaining sol is simply shaken off, and the anode is air-dried for 3 hours, then dried in a 60℃ oven for 30 minutes. Finally, it is placed in a muffle furnace for thermal decomposition at 550℃ for 1.5 hours. After cooling to room temperature, a noble metal-coated titanium anode with a manganese titanate intermediate layer is obtained. Relevant tests are performed, and the results are as follows: Figure 15-16 As shown.
[0156] Figure 15This is a scanning electron microscope image of the tin-lead coated titanium anode with a manganese titanate intermediate layer prepared in Example 3. It can be seen that the catalytic active layer is uniformly coated, with a particle diameter of 20-30 nm, no obvious cracks or broken structures, and good compactness.
[0157] Figure 16 This is a resistivity test diagram of the tin-lead coated titanium anode with a manganese titanate interlayer prepared in Example 3 in an electrochemical system. Its resistance was measured using an electrochemical workstation. A three-electrode system was used, with the working electrode being the newly prepared electrode of Example 3 with a diameter of 2.0 cm × 1.0 cm, the counter electrode being a carbon plate electrode, and the reference electrode being a silver / silver chloride electrode (Ag / AgCl). The electrolyte was a 7.5 wt% sodium sulfate solution containing 0.1 wt% sulfuric acid.
[0158] Example 4
[0159] The tin-lead coated titanium anode with a manganese titanate interlayer prepared in Example 3 was used for the electrochemical degradation of p-bromophenol wastewater.
[0160] The wastewater electrochemical degradation treatment was carried out in an electrolytic cell using a dual-electrode system. The working electrode was a tin-lead coated titanium anode electrode with a manganese titanate interlayer, prepared in Example 3, measuring 2.0 cm × 1.0 cm. The counter electrode was a carbon plate electrode, with a current density of 200 A / m. 2 Under conditions of stainless steel cathode and an electrode spacing of 3 cm, experiments were conducted on simulated organic wastewater containing p-bromophenol as the standard molecule to degrade organic matter. The sodium sulfate content was 7.5 wt%, and the p-bromophenol content was approximately 250 mg / L. Samples were taken every 30 minutes to test the degradation rate of p-bromophenol.
[0161] The removal efficiency of p-bromophenol after 6 hours of electrolysis is as follows: Figure 17 As shown in Table 3, the removal rate of bromophenol is as high as 85%.
[0162] Table 3 shows the liquid chromatography sampling data of the electrochemical degradation of bromophenol by the lead-antimony coated titanium anode plate with a manganese titanate interlayer in Example 3.
[0163]
[0164]
[0165] Comparative Example 4
[0166] In the comparative study, commercial lead-titanium anode plates were used as the anode to further reduce the current density and avoid high energy consumption caused by high-power operation. NaCl was added as an electrolyte additive at a content of 0.2 wt%. The removal efficiency of p-bromophenol after six hours of electrolysis was as follows: Figure 17 As shown.
[0167] according to Figure 17 As shown in Table 3, the p-bromophenol removal rate of the comparative commercial lead-titanium anode plate was 72.0%, while the p-bromophenol removal rate of the titanium anode prepared in Example 4 was close to 90%. The results indicate that the p-bromophenol removal effect of the lead-antimony coated titanium anode plate with a manganese titanate interlayer is comparable to that of the commercial lead-titanium anode, and the completion time can be shortened by nearly half.
[0168] The specific embodiments described above further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above descriptions are merely specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing a coated titanium anode with a titanate interlayer, comprising: A first metal source, a first sol, a first film-forming agent, and a first acid-base regulator are dispersed in an aqueous solution to obtain an intermediate layer sol solution, wherein the first metal source is a soluble salt of a first metal. The titanium substrate is immersed in the intermediate layer sol solution and subjected to a first heat treatment, so that the titanate intermediate layer of the first metal is grown in situ on the surface of the titanium substrate. A second metal source, a second sol, a second film-forming agent, and a second acid-base regulator are dispersed in an aqueous solution and then subjected to heating and complexation to obtain a surface catalytic layer sol solution, wherein the second metal source is a soluble salt of a second metal. The titanium substrate with the titanate intermediate layer is immersed in the surface catalyst layer sol solution and subjected to a second heat treatment, so that the oxide catalyst layer of the second metal is grown in situ on the surface of the titanate intermediate layer, thereby obtaining the coated titanium anode. The first metal is manganese, and the second metal is one of the following combinations: iridium and ruthenium, tin and lead; The first film-forming agent and the second film-forming agent are each independently at least one of polyethylene glycol and polyvinyl alcohol; The first sol and the second sol are polyvinylpyrrolidone; The acidic agent of the first acid-base regulator and the second acid-base regulator are each independently at least one of dilute nitric acid, dilute hydrochloric acid, dilute sulfuric acid and acetic acid, and the alkaline agent is each independently at least one of dilute ammonia, potassium monohydrogen phosphate and sodium monohydrogen phosphate. The amounts of the first and second acid-base adjusters are such that the pH of the prepared intermediate layer sol solution is between 1.5 and 2.5, and the pH of the surface catalyst layer sol solution is between 5 and 7.
2. The preparation method according to claim 1, wherein, The first metal source is added in the form of a nitrate or chloride of the first metal; the second metal source is added in the form of a nitrate or chloride of the second metal. In the preparation of the surface catalyst layer sol solution, a complexing agent is also added when the solution is dispersed in an aqueous solution.
3. The preparation method according to claim 2, wherein, The complexing agent is at least one of citric acid, sodium citrate, and potassium citrate.
4. The preparation method according to claim 1 further includes: Before immersing the titanium substrate into the intermediate sol solution, the titanium substrate is pretreated, wherein the pretreatment includes the following operations: The titanium substrate is cleaned, etched, and then stored in an oxygen-free environment for later use.
5. The preparation method according to claim 1, wherein, The temperature for the heating complexation is 50-60 ℃; The first heat treatment operation includes: The titanium matrix impregnated with the intermediate sol solution is dried and calcined. The drying temperature is 25-60 ℃ and the drying time is 4-6 h. The calcination temperature is 300-500 ℃ and the calcination time is 1.5-3 h. The titanium matrix impregnated with the intermediate sol solution after drying and calcination is subjected to cooling reduction at a temperature of 100-300℃ in a hydrogen-argon mixture atmosphere for 1-3 hours. The second heat treatment operation includes: The titanium substrate with the titanate intermediate layer grown after being immersed in the surface catalyst sol solution is dried and calcined. The drying temperature is 25-60 ℃ and the drying time is 4-6 h. The calcination temperature is 350-500 ℃ and the calcination time is 0.5-2 h.
6. The preparation method according to claim 2, wherein, In the intermediate sol solution, the total content of the first metal source is 5-20 wt%; In the catalyst layer sol solution, the total content of the second metal source is 5-20 wt%; The molar ratio of the complexing agent to the second metal source metal element is 0.6-1.0:
1.
7. The preparation method according to claim 1, wherein, In the intermediate layer sol solution, the ratio of intermediate layer sol solution:sol mass:film-forming agent mass is 1ml:0.02-0.10g:0.02-0.10g; In the surface catalytic layer sol solution, the ratio of surface catalytic layer sol solution: sol mass: film-forming agent mass is 1 ml: 0.02-0.10 g: 0.02-0.10 g.
8. A coated titanium anode having a titanate intermediate layer, prepared by the method according to any one of claims 1 to 7.
9. An application of a coated titanium anode having a titanate interlayer as described in claim 8, wherein, When the second metal is iridium and ruthenium, the application is water electrolysis; When the second metal is tin or lead, the application is the electrochemical degradation of bromophenol.